Determinants of quality of life in healthy girls with menstrual disorders against healthy peers - Zięba, Ewa; Markowska, Małgorzata; Krawczyńska, Jadwiga; Król, Halina; Nowak - Starz, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Adolescent girls need contact with their peers in order to build a pattern of social relationships, which they will use in adult life. It is the peers that are expected to meet their needs for acceptance and support. The experiences acquired in the school environment affect the development of adolescents in many areas. The aim of the study. To examine the correlation between the quality of life of girls with menstrual disorders in the light of questionnaire KIDSCREEN-52, and their age, selected indicators of physical health and selected socio-economic indicators against healthy peers. Material and methods. We examined 122 girls with menstrual disorders (group I) from urban and rural environments and 240 girls without the disorders in health and development (group II) from primary and lower secondary schools from urban and rural environments. The examined girls who attended primary and lower secondary schools were between the age of 13 and 16. The method of diagnostic poll along with the questionnaire interview technique were used, as well as the following research tools: KIDSCREEN-52 Health Related Quality of Life Questionnaire for Children and Young People — the Polish version of the questionnaire for research on the quality of life connected with the health of children and adolescents; A survey of the author’s construction containing questions concerning the socio-economic situation of the examined (FAS scale) Anthropometric measurement techniques were used for obtaining somatometric data. Results. The largest number of dependencies between the dimensions of life quality related to health and age was observed on the basis of the analysis of the results obtained. Dissatisfaction with life and socio-economic status proved to be an equally important determinant of poor evaluation of quality of life in health. Conclusions. There exists a high correlation between the dimensions of quality of life related to health according to questionnaire KIDSCREEN-52, and age, selected indicators of physical health and socio-demographic indicators in girls from diversified environments with menstrual disorders and no disorders in health and development. Diseases and negligence in care over the population at developmental age, in each stage of their development, and especially in the period of adolescence, have multiple negative health, social and economic effects both at present as well as in future generations. Hence the meaningfulness of using subjective health indexes in assessment of the quality of life connected with the health of girls with menstrual disorders.